Dear Rafe = Mi querido Rafa - Hinojosa, Rolando (Hinojosa, Rolando. Klail City death trip series., 2005)
"Welcome to Klail City, in Belken County, along the Mexican border in Texas' Rio Grande Valley. In the weeks leading up to the Democratic primary, Jehu Malacara pens letters to his cousin Rafe Buenrostro chronicling the political rabble-rousing of Klail City's wealthiest citizens. In the process he explores the complex web of relationships among the who's who of Belken. At the center is Noddy Perkins, who decides on bank loans and business investments, club memberships, and local politics for the privileged few who control the political and economic landscape of the community." "When Malacara turns up missing, and writer P. Galindo begins interviewing the citizens to find out about his disappearance, tales of deceit and betrayal float to the surface. From Jehu's knockout girlfriend, Ollie, to up-and-coming socialite, Becky Escobar, and even to old man Perkins himself, Hinojosa offers a feast of quirky characters and misdeeds."--BOOK JACKET.